Depression Symptoms Improve after Successful Weight Loss with Emotional Freedom Techniques. (28th July 2013) - Stapleton, Peta; Church, Dawson; Sheldon, Terri; Porter, Brett; Carlopio, Cassandra
Abstract : Ninety-six overweight or obese adults were randomly allocated to a four-week EFT treatment or waitlist condition. Waitlist participants crossed over to the EFT group upon completion of wait period. Degree of food craving, perceived power of food, restraint capabilities, and psychological symptoms were assessed at pretreatment, posttreatment and at 12-month follow-up for combined EFT groups. Significant improvements in weight, body mass index, food cravings, subjective power of food, craving restraint and psychological coping for EFT participants from pretreatment to 12-month follow-up (P < 0.05 ) were reported. The current paper isolates the depression symptom levels of participants, as well as levels of eight other psychological conditions. Significant decreases from pre- to posttreatment were found for depression, interpersonal sensitivity, obsessive-compulsivity, paranoid ideation, and somatization (P < 0.05 ). Significant decreases from pretreatment to 12-month follow-up were found for depression, interpersonal sensitivity, psychoticism, and hostility. The results point to the role depression, and other mental health conditions may play in the successful maintenance of weight loss.